Management of Multiple Recession simultaneously with Modified Coronally Advanced Flap - Shah, Harish Kumar; Chaudhary, Shashi Kant; Goel, Khushboo; Shrestha, Sajeev (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Gingival recession is one of the aesthetic concern for a beautiful smile. In an aesthetically driven era, root coverage requires consideration of all prognostic factors for successful results. This paper reports a case of treatment of Miller’s Class I gingival recession involving multiple teeth. A modified coronally advanced flap procedure was performed. At the postoperative follow-up visits, healing was uneventful. After 9 months, excellent aesthetic result was achieved with complete root coverage. Periodontal health was normal and the patient was satisfied with the result.